DETERMINAN FEE AUDIT PADA KAP DI JAWA TIMUR - Kholilah, Kholilah (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
This study sets out to examine factors influencing audit fees paid on public accountant firm (KAP) in East Java. Data were collected from 2012 company annual reports audited by KAP. An audit fee models using a sample of 84 audited financial reports by using multiple linear regression analysis. The findings show a direct relationship between audit fees and each of corporate size and audit location, an inverse relationship has been detected between audit fees and each of audit risk and seasonality, the findings also revealed that audit fees are not significantly influenced by KAP switching.